The decagonal AlCuRh quasicrystal modelled with five atomic surfaces – high‐temperature X‐ray diffraction data analysis. Issue 5 (8th July 2022) - Buganski, Ireneusz; Strzalka, Radoslaw; Wolny, Janusz
Abstract : The anomalous thermal dependence of lattice constants is linked to the occupancy of the new fifth atomic surface. The emergence of the extra atomic surface and its impact on the structure is treated with the distribution moments analysis. Abstract : Five datasets of high‐temperature X‐ray diffraction performed upon the decagonal phase of AlCuRh are used to derive the temperature‐related structural changes. Two sets of atomic structure refinements are conducted, with four and five atomic surfaces, respectively. The fifth atomic surface emerges as a consequence either of the transition to a tiling with different local isomorphism than the Penrose tiling or of the structure being phason disordered. The correlation of the occupancy of the fifth atomic surface with the thermal dependence of the lattice constants is 80%. In addition, the structural refinement with five atomic surfaces allowed a better agreement with the experimental data to be obtained, compared with the model with four atomic surfaces.